EARLY DETECTION OF BREAST CANCER WITH “SADARI” PEMERIKSAAN PAYUDARA SENDIRI - Aini, Aisyiah Nur; Nagari, Elvira Puspa; Purwaningsih, Heni; Sulastri, S; Mintarsih, Sri (Prosiding University Research Colloquium, 2024)
Breast cancer stands as a major health threat for women, often diagnosed as the most common cancer and the second leading cause of death among women. With its prevalence continually rising globally, breast cancer registers 18.1 million new cases and 9.6 million deaths annually. Global Cancer Observatory data for 2018 indicates 2,088,849 new cases and 626,679 deaths due to breast cancer among women worldwide. Breast Self-Examination (BSE), playing a crucial role in early detection, reveals that 85% of breast lumps are discovered by the individuals themselves. Previous research highlights that breast cancer cases in Kota Kupang are predominantly found in women aged 25-35, while late adolescents (17-22 years old) are also at risk. Therefore, prevention is advocated from a young age. Early detection methods such as BSE, clinical breast examination, and mammography are key in preventive efforts and intervention. BSE, as a simple and cost-effective method, empowers women to independently examine their breast conditions, detecting changes that may indicate breast cancer. Community engagement is conducted to provide information and understanding to the public about the significance of early detection of breast cancer through BSE, as a tangible step in reducing mortality rates associated with this disease. Keywords: Breast cancer 1; SADARI 2;